2003
DOI: 10.2741/1098
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte responses are critical determinants in the pathogenesis and resistance to mycoplasma respiratory disease

Abstract: Mycoplasmas are responsible for many human and animal respiratory diseases and have a tremendous economic and health impact worldwide. Currently, there is no vaccine against any animal or human mycoplasma species. Despite the vast amount of research, the mechanisms that control hosts' resistance and susceptibility to mycoplasma infection remains unclear. Immune responses, particularly T lymphocyte responses, are believed to be critical players in the pathogenesis of mycoplasma disease. In this review, we will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 156 publications
0
13
0
Order By: Relevance
“…Using murine infection with M. pulmonis, the importance of lymphocytes in contributing to the pathology of mycoplasma inflammatory lung disease was demonstrated (21). For example, SCID or nude mice (lacking either T and B cells or T cells alone) infected with M. pulmonis display reduced inflammatory damage (22,23). The depletion of CD4 ϩ , but not CD8 ϩ , T cells reduces disease severity in susceptible (i.e., BALB/c) mice and confirms that T cells dictate the outcome of infection (24).…”
mentioning
confidence: 86%
“…Using murine infection with M. pulmonis, the importance of lymphocytes in contributing to the pathology of mycoplasma inflammatory lung disease was demonstrated (21). For example, SCID or nude mice (lacking either T and B cells or T cells alone) infected with M. pulmonis display reduced inflammatory damage (22,23). The depletion of CD4 ϩ , but not CD8 ϩ , T cells reduces disease severity in susceptible (i.e., BALB/c) mice and confirms that T cells dictate the outcome of infection (24).…”
mentioning
confidence: 86%
“…As with other mycoplasma diseases, M. pulmonis disease has an immunopathologic element to disease progression. In fact, elements of both the innate [9], [10], [11] and adaptive [12], [13], [14] arms of the immune system play a role in the progression and intrapulmonary clearance of the disease. Thus, it is clear that the mechanisms governing the recruitment of inflammatory cells and control of mycoplasma infection will ultimately determine the severity of mycoplasma respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that elements of the adaptive immune response contribute to the pathology (58, 59), while some responses are protective against M. pulmonis infections (1, 20). Importantly, these responses are determined by the activation of different T cell populations, and the mechanisms that initiate these responses are critical in the pathogenesis of mycoplasma respiratory disease of the lower respiratory tract (19, 60). In a previous study (34), we found that dendritic cells are the major APC population responsible for pulmonary T cell stimulation in mycoplasma-infected mice and likely contribute to responses impacting disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%